Vocal behaviour, parasitic infection, chronic stress and body condition in rufous‐naped wrens (Campylorhynchus rufinucha). (31st August 2022) - Meza‐Montes, Estefanía; Fernández‐Gómez, Ronald A.; Llanes‐Quevedo, Alexander; Navarro‐Sigüenza, Adolfo G.; Santiago‐Alarcon, Diego; Sosa‐López, J. Roberto
Abstract : We explored the relationship between haemosporidian infection (infected vs. uninfected), parasite load, heterophil:lymphocyte ratio, body condition and vocal behaviour of the Rufous‐naped Wren Campylorhynchus rufinucha . Our results, albeit based on a small sample size, showed no evidence of an association between vocal behaviour and infection status, heterophil:lymphocyte ratio or body condition. Infections did not vary between localities. Our results showed, however, that infection status was associated with a higher song rate, and that in males and females belonging to the same reproductive pair there was a strong positive correlation in terms of infection status and parasite load. Abstract : En este estudio exploramos la relación entre la infección por hemosporidios (infectados vs. no infectados), la carga parasitaria, la proporción de heterófilos‐linfocitos, la condición corporal y el comportamiento vocal de la Matraca Nuca Canela Campylorhynchus rufinucha. Nuestros resultados, aunque basados en un tamaño de muestra pequeño, no mostraron evidencia de una asociación entre el comportamiento vocal y el estado de infección, la relación heterófilo:linfocito, o la condición corporal. Las infecciones no variaron entre las localidades. Sin embargo, nuestros hallazgos mostraron que las aves infectadas tenían una mayor tasa de canto que las no infectadas, y que los machos y las hembras pertenecientes a la misma pareja reproductiva tenían una fuerte correlación positiva en el estado de infección y la carga parasitaria.